Transient Expression of CRISPR/Cas9 Machinery Targeting TcNPR3 Enhances Defense Response in Theobroma cacao - Fister, Andrew S.; Landherr, Lena; Maximova, Siela N.; Guiltinan, Mark J. (Frontiers in Plant Science, 2018)
Theobroma cacao, the source of cocoa, suffers significant losses to a variety of pathogens resulting in reduced incomes for millions of farmers in developing countries. Development of disease resistant cacao varieties is an essential strategy to combat this threat, but is limited by sources of genetic resistance and the slow generation time of this tropical tree crop. In this study, we present the first application of genome editing technology in cacao, using Agrobacterium-mediated transient transformation to introduce CRISPR/Cas9 components into cacao leaves and cotyledon cells. As a first proof of concept, we targeted the cacao Non-Expressor of Pathogenesis-Related 3 (TcNPR3) gene, a suppressor of the defense response. After demonstrating activity of designed single-guide RNAs (sgRNA) in vitro, we used Agrobacterium to introduce a CRISPR/Cas9 system into leaf tissue, and identified the presence of deletions in ~30% of TcNPR3 copies in the treated tissues. The edited tissue exhibited an increased resistance to infection with the cacao pathogen Phytophthora tropicalis and elevated expression of downstream defense genes. Analysis of off-target mutagenesis in sequences similar to sgRNA target sites using high-throughput sequencing did not reveal mutations above background sequencing error rates. These results confirm the function of NPR3 as a repressor of the cacao immune system and demonstrate the application of CRISPR/Cas9 as a powerful functional genomics tool for cacao. Several stably transformed and genome edited somatic embryos were obtained via Agrobacterium-mediated transformation, and ongoing work will test the effectiveness of this approach at a whole plant level.